Cases in international relations - Snow, Donald M., 1943- (Pearson Longman, 2012)
Designed to complement the main themes of any introductory course, this bestselling text presents 16 original case studies that survey the state of the international system and look in-depth at issues of current interest. Cases in International Relations offers more than a collection of journal articles; it provides a coherent and accessible approach that encourages students to put international relations concepts to practical use.